Kálmán’s filtering technique in structural equation modeling - BOLLA, Marianna; ABDELKHALEK, Fatma (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
The goal of this note is to present a new shorter proof for the maximal monotonicity of the Minkowski sum of two maximal monotone multi-valued operators defined in a reflexive Banach space under the classical interiority condition involving their domains. Mathematics Subject Classification (2010): 47H05, 46N10.